New English File. Elementary: Student's Book - Oxenden C. Clive (Oxford, Oxford University Press, 2011)
The completely new editions of English File 1 and 2, based on the principles that have made English File so popular. Key features 100% new lessons that work, that are fun, and that get students talking. An expanded Vocabulary Bank. A new Grammar Bank section with rules and exercises. Practical English lessons, a focus on functional language supported by the New English File Study Link Videos. The same unequalled level of teacher support. More photocopiable materials for teachers, with an extra grammar and communicative activity for every lesson.